Solid lipid particle-based tablets for buccal delivery: The role of solid lipid particles in drug release - Le, Ngan D.T.; Tran, Phuong H.L.; Lee, Beom Jin; Tran, Thao T.D. (Journal of Drug Delivery Science and Technology, 2019)
This study aims to develop mucoadhesive tablets containing solid lipid particles for controlled release pattern through buccal delivery. The buccal tablets containing drug-loaded solid lipid particles (SLPs) were fabricated using the ultrasonication method and lyophilisation with the incorporation of bioadhesive excipients. The role of stearic acid in the lipid phase and the effects of different surfactant contents were thoroughly evaluated. The stearic acid in formulations showed its impacts on particle formation and release characteristics. Although liquid surfactants could create SLPs of nano-size, the dissolution profile resulted in low drug release. The combination of a solid surfactant and a liquid surfactant resulted in better tablet formation and an improvement in the dissolution rate of prednisolone in both immediate release and sustained release. Furthermore, an adaptable pH surface, long mucoadhesion time, and satisfactory permeation resulted in suitable conditions for buccal tablet design without causing any irritations. The success of this work could contribute to a new strategy for improving the bioavailability of poorly water-soluble drugs by buccal delivery.
Keywords: Buccal tablet; Immediate release; Solid lipid particle; Sustained release